An improved indoor location algorithm based on linear interpolation - Mengdan ZHANG; Guangyue LU; Honggang WANG; Jiming LIU (Dianxin kexue)
Aiming at the shortcomings of heavy workload in the off-line phase,limited positioning accuracy and poor robustness of indoor location fingerprint positioning technology,an improved fingerprint matching algorithm based on linear interpolation was proposed.Compared with the traditional location fingerprint positioning technology,it reduced the overall workload as well as the bad effects caused by muti-path effect.At last,a lab scene was set up to test the positioning performance of this algorithm.It is shown by the test that the average positioning accuracy of this algorithm has been improved by 34.25% compared with that of WKNN method,and the positioning accuracy error ratio of most points to be test is within 0.4 m,the positioning accuracy,robustness and adaptability in environment change were demonstrated.